The Protective Roles of Estrogen Receptor β in Renal Calcium Oxalate Crystal Formation via Reducing the Liver Oxalate Biosynthesis and Renal Oxidative Stress-Mediated Cell Injury. (17th April 2019) - Zhu, Wei; Zhao, Zhijian; Chou, Fu-Ju; Zuo, Li; Liu, Tongzu; Bushinsky, David; Chang, Chawnshang; Zeng, Guohua; Yeh, Shuyuan
Abstract : Females develop kidney stones less frequently than males do. However, it is unclear if this gender difference is related to altered estrogen/estrogen receptor (ER) signaling. Here, we found that ER beta (ER β ) signals could suppress hepatic oxalate biosynthesis via transcriptional upregulation of the glyoxylate aminotransferase (AGT1) expression. Results from multiple in vitro renal cell lines also found that ER β could function via suppressing the oxalate-induced injury through increasing the reactive oxygen species (ROS) production that led to a decrease of the renal calcium oxalate (CaOx) crystal deposition. Mechanism study results showed that ER β suppressed oxalate-induced oxidative stress via transcriptional suppression of the NADPH oxidase subunit 2 (NOX2) through direct binding to the estrogen response elements (EREs) on the NOX2 5 ′ promoter. We further applied two in vivo mouse models with glyoxylate-induced renal CaOx crystal deposition and one rat model with 5% hydroxyl-L-proline-induced renal CaOx crystal deposition. Our data demonstrated that mice lacking ER β (ER β KO) as well as mice or rats treated with ER β antagonist PHTPP had increased renal CaOx crystal deposition with increased urinary oxalate excretion and renal ROS production. Importantly, targeting ER β -regulated NOX2 with the NADPH oxidase inhibitor, apocynin, can suppress the renal CaOx crystal deposition in the in vivo mouse model. Together, results from multiple in vitro cell lines and in vivo mouse/rat models all demonstrate that ER β may protect against renal CaOx crystal deposition via inhibiting the hepatic oxalate biosynthesis and oxidative stress-induced renal injury.